(untitled) (Biological Sciences - PJSIR, 2022)
The laboratory studies were undertaken to evaluate the repellent effect of different plant materials i.e. lemon, neem, nerium, Acacia, Eucalyptus at 6% concentration (w/w) against Callosobruchus maculatus on chickpea. In addition, the corrected mortality and seed characteristics (seed germination %, root length and seed vigor Index) were also observed. The results showed a repellent effect with an index value of RI=0.8 for lemon and Eucalyptus at 24 h. The overall corrected mortality showed the highest (24.73%) at neem and the lowest (4.30%) at Eucalyptus. The seed characteristics showed that storage of chickpea seeds until two months was ideal. The best results were recorded after one month of preservation in Acacia and control with maximum germination (100%), root length (2.18±0.06 and 3.25±0.11 cm) and V.I (219.0 and 326.0) followed by neem with germination of 96.67% and lemon with root length of 2.37±0.18 cm and V.I 222.13. Thus, it is concluded that all plant materials were not good repellent for pulse beetle, whereas, neem extract displayed an efficient efficacy to kill the pest and lemon showed an ideal repellent effect.